Melville’s Ahab in Moby Dick and R K Narayan’s Vasu in The Man-eater of Malgudi: A Quest to Enter a “New World” - Sharma, Vipin K (SCAD Independent, 2023)
Utilizing critical literature on Melville and RK Narayan and then reading Moby-Dick (1851) and The Man Eater of Malgudi closely (1961), this article concerns American and Indian works of literature and argues that both writers were among the leading imaginative writers to create niches in terms of philosophy. Both used imagination, symbolism, and spiritual and universal impulses to make the characters and books worth reading. However, both novels portray a quest to enter a “New World” through protagonists Ahab and Vasu, who bring multiple concerns and commit catastrophic blunders. The article sails through a comparative study of the protagonists analyzing the critical factors, such as adventurous and mysterious wanderers, the universe being both godless and purposeless, virtues versus sins, influence and fusion of divergent subjects, their anti-life and anti-nature attitude, intelligence and wisdom and archetype ambitions that lead them to self-destruction. This paper intends to explore the dynamics of the relationship between American and Indian Literature through protagonists Ahab and Vasu’s acquisitive, coseismic, nomadic, and fanatic nature in their quest to enter a “New World” to address aspects that the present time calls for; hence, making both novels great in the twenty-first century.